Exploring how the level of ethnic diversity and segregation in Faculty of Medicine, Health Sciences, and Pharmacy courses affects the size of the Ethnicity Attainment Gap. : International Summer Conference: Inequalities in Medicine, In2MedSchool (I2MS), 2nd July 2022. - Bello, Oyinkansola; Mbaki, Yvonne; Kokolski, Marie; Anderson, Susan (Advanced Journal of Professional Practice, 2023)
Background:Research shows multifaceted / poorly understood causes of the Ethnicity Attainment Gap (EAG) between White & Black, Asian, and Minority Ethnic (BAME) students within the UK. Mclean's (2013) study on EAG found it grows throughout the course due to university factors. This paper investigates the Powell Diversity Rationale Hypothesis — whether ethnic diversity and segregation in The Faculty of Medicine, Health Science and Pharmacy (TFMHSP) courses affect the EAG. Method:Ethical approval gained; a survey was distributed to 1000+ students. In categories concerning belonging, discrimination and ethnic segregation, data analysis revealed significant discrepancies between BAME/White students' responses. Using Kivlighan’s Diversity Index, an objective measure of ethnic diversity determined the most (Medical Physiology and Therapeutics (MPT)) and least (Biology) diverse courses, both were compared using established themes and perceived attainment. Findings:Responses were representative of the ethnicity split of the 2018 cohort (63.46% White and 35.58% BAME). BAME MPT/Biology students had no significant differences in their perceived grades compared to White students and both reported no ethnic representation in university leadership e.g., academic staff. Other areas where BAME student experience was poorer concerned facing discrimination/harassment. A 2021 redistribution of the survey revealed that Covid-19 may influence the EAG, but only short-term changes were observed. Conclusions:Ethnic diversity does not reduce EAG based on perceived attainment. Recommendations for further research to identify/address the reasons of the EAG include employing real grades/focus groups. These aim to improve the university environment & build well-rounded healthcare professionals.